Pharmacokinetics of desflurane uptake and disposition in piglets - Lu, Chih-Cherng; Ho, Shung-Tai; Hu, Oliver Yao-Pu; Hsiong, Cheng-Huei; Cheng, Yuan-Chen; Hsu, Che-Hao; Lin, Tso-Chou (Frontiers in Pharmacology, 2024)
Aim: Many respiratory but few arterial blood pharmacokinetics of desflurane uptake and disposition have been investigated. We explored the pharmacokinetic parameters in piglets by comparing inspiratory, end-tidal, arterial blood, and mixed venous blood concentrations of desflurane.Methods: Seven piglets were administered inspiratory 6% desflurane by inhalation over 2 h, followed by a 2-h disposition phase. Inspiratory and end-tidal concentrations were detected using an infrared analyzer. Femoral arterial blood and pulmonary artery mixed venous blood were sampled to determine desflurane concentrations by gas chromatography at 1, 3, 5, 10, 20, 30, 40, 50, 60, 80, 100, and 120 min during each uptake and disposition phase. Respiratory and hemodynamic parameters were measured simultaneously. Body uptake and disposition rates were calculated by multiplying the difference between the arterial and pulmonary artery blood concentrations by the cardiac output.The rates of desflurane body uptake increased considerably in the initial 5 min (79.8 ml.min-1) and then declined slowly until 120 min (27.0 ml.min-1). Similar characteristics of washout were noted during the subsequent disposition phase. Concentration-time curves of end-tidal, arterial, and pulmonary artery blood concentrations fitted well to zero-order input and first-order disposition kinetics. Arterial and pulmonary artery blood concentrations were best fitted using a two-compartment model. After 2 h, only 21.9% of the desflurane administered had been eliminated from the body.Conclusions: Under a fixed inspiratory concentration, desflurane body uptake in piglets corresponded to constant zero-order infusion, and the 2-h disposition pattern followed firstorder kinetics and best fitted to a two-compartment model.